Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

End-of-life pathology in UM-HET3 mice treated with 16 α‑hydroxyestradiol or late‑start canagliflozin - Jessica M. Snyder; David E. Harrison; Ron Korstanje; Brett Ginsburg; Peter C. Reifsnyder; James Nelson; Scott Leiser; Catherine Kaczorowski; Denise M. Imai; Adam B. Salmon; Randy Strong; Warren Ladiges; et al. (GeroScience, 2025)
Canagliflozin (Cana) started at 16 months of age and 16-hydroxy-estradiol (OH_Est) started at 12 months each led to significant increases in lifespan in male UM-HET3 mice but significant decreases in female lifespan. To seek insights into the basis for these sex-specific effects, we performed end-of-life histopathological analyses of control and treated mice for all three interventions testing program sites. There were no significant drug-induced alterations in inferred cause of death, although statistical power was low for such comparisons. Tabulation of incidental lesions (i.e., combining lethal and non-lethal lesions) revealed a complex set of significant and near-significant changes caused by each of the two agents, in some cases absent, or even opposite in direction, in one of the two sexes. The analysis did not, however, reveal a clear pattern that would explain the selective sex-specific effects of either agent on lifespan. It is plausible that the female-specific harm induced by each of these agents could reflect harmful or toxic effects that are not easily detectable by histopathological examination.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

The Gehan test identifies life-extending compounds overlooked by the log-rank test in the NIA Interventions Testing Program: Metformin, Enalapril, caffeic acid phenethyl ester, green tea extract, and 17-dimethylaminoethylamino-17-demethoxygeldanamycin hydrochloride - Nisi Jiang; Jonathan Gelfond; Qianqian Liu; Randy Strong; James F. Nelson (GeroScience, 2024)
The National Institute on Aging Interventions Testing Program (ITP) has so far identified 12 compounds that extend the lifespan of genetically heterogeneous mice using the log-rank test. However, the log-rank test is relatively insensitive to any compound that does not uniformly reduce mortality across the lifespan. This test may thus miss compounds that only reduce mortality before midlife, for example, a plausible outcome if a compound only mitigates risk factors before midlife or if its efficacy is reduced at later ages. We therefore reanalyzed all data collected by the ITP from 2004–2022 using the Gehan test, which is more sensitive to mortality differences earlier in the life course and does not assume a uniformly reduced mortality hazard across the lifespan. The Gehan test identified 5 additional compounds, metformin, enalapril, 17-dimethylaminoethylamino-17-demethoxygeldanamycin hydrochloride (17-DMAG), caffeic acid phenethyl ester (CAPE), and green tea extract (GTE), which significantly increased survival but were previously missed by the log-rank test. Three (metformin, enalapril, and 17-DMAG) were only effective in males and two (CAPE and GTE) were only effective in females. In addition, 1,3-butanediol, which by log-rank analysis increased survival in females but not males, increased survival in males by the Gehan test. These results suggest that statistical tests sensitive to non-uniformity of drug efficacy across the lifespan should be included in the standard statistical testing protocol to minimize overlooking geroprotective interventions.

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Castration reduces mortality and increases resilience in male mice: what is next? - Nisi Jiang; Catherine J. Cheng; Randy Strong; James F. Nelson (GeroScience, 2023)

Long-term effects of canagliflozin treatment on the skeleton of aged UM-HET3 mice - Gozde Yildirim; Edmara T. P. Bergamo; Sher Bahadur Poudel; Ryan R. Ruff; Manisha Dixit; Bin Hu; Dindo Q. Mijares; Lukasz Witek; Carolyn Chlebek; David E. Harrison; Randy Strong; Richard A. Miller; et al. (GeroScience, 2023)

Canagliflozin retards age-related lesions in heart, kidney, liver, and adrenal gland in genetically heterogenous male mice - Jessica M. Snyder; Kerriann M. Casey; Andrzej Galecki; David E. Harrison; Hashan Jayarathne; Navasuja Kumar; Francesca Macchiarini; Nadia Rosenthal; Marianna Sadagurski; Adam B. Salmon; Randy Strong; Richard A. Miller; et al. (GeroScience, 2023)
Canagliflozin (Cana), a clinically important anti-diabetes drug, leads to a 14% increase in median lifespan and a 9% increase in the 90th percentile age when given to genetically heterogeneous male mice from 7 months of age, but does not increase lifespan in female mice. A histopathological study was conducted on 22-month-old mice to see if Cana retarded diverse forms of age-dependent pathology. This agent was found to diminish incidence or severity, in male mice only, of cardiomyopathy, glomerulonephropathy, arteriosclerosis, hepatic microvesicular cytoplasmic vacuolation (lipidosis), and adrenal cortical neoplasms. Protection against atrophy of the exocrine pancreas was seen in both males and females. Thus, the extension of lifespan in Cana-treated male mice, which is likely to reflect host- or tumor-mediated delay in lethal neoplasms, is accompanied by parallel retardation of lesions, in multiple tissues, that seldom if ever lead to death in these mice. Canagliflozin thus can be considered a drug that acts to slow the aging process and should be evaluated for potential protective effects against many other late-life conditions.

San Antonio Nathan Shock Center: your one-stop shop for aging research - Adam B. Salmon; James F. Nelson; Jonathan A. L. Gelfond; Martin Javors; Brett Ginsburg; Marisa Lopez-Cruzan; Veronica Galvan; Elizabeth Fernandez; Nicolas Musi; Yuji Ikeno; Gene Hubbard; James Lechleiter; et al. (GeroScience, 2021)

Correction to: Hydrogen sulfide ameliorates aging-associated changes in the kidney - Hak Joo Lee; Denis Feliers; Jeffrey L. Barnes; Sae Oh; Goutam Ghosh Choudhury; Vivian Diaz; Veronica Galvan; Randy Strong; James Nelson; Adam Salmon; Christopher G. Kevil; Balakuntalam S. Kasinath (GeroScience, 2021)

Hydrogen sulfide ameliorates aging-associated changes in the kidney - Hak Joo Lee; Denis Feliers; Jeffrey L. Barnes; Sae Oh; Goutam Ghosh Choudhury; Vivian Diaz; Veronica Galvan; Randy Strong; James Nelson; Adam Salmon; Christopher G. Kevil; Balakuntalam S. Kasinath (GeroScience, 2018)